Analysis Of Students' Difficulties In Writing Recount Texts At The Secend Semester Of Institut Penddikan Nusantara Gelobal Academic Year 2022/2023 - Muhsinin, Muhsinin (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
Problems often faced by students when writing. They often get stuck and seem to have difficulty expressing their ideas in written form. From the assessments carried out by lecturers, students often find many errors in writing chapter reports. Finally, the most common errors are found in content aspects, such as grammar, vocabulary, punctuation, etc. What are the students' difficulties in writing recount texts for the even semester of the Gelobal Nusantara Education Institute for the 2022/2023 academic year?" The aim of this research is to determine students' abilities and to investigate students' difficulties in writing recount texts. In this research, researchers took the second semester as the subject. The second semester class consists of 25 students, in this case the researcher took 3 second semester students for a writing test and interview as an instrument for this research. The results of the research show that the results that can be interpreted are that the difficulties faced by students are still grammatical difficulties, spelling errors, and they have limited vocabulary to choose appropriate diction. It is recommended for lecturers to provide more practice in writing to improve students' vocabulary and grammar in writing recount texts